Characterisation of physicochemical properties of mango infected by Colletotrichum gloeosporioides - Sudau, E. T.; Norhashila, H.; Siti, K. B.; Siti, I. I.; Maimunah, M. A. (Rynnye Lyan Resources, 2025)
Mangoes are highly vulnerable to various diseases, both before and after harvest. One of the fungal maladies impacting mango trees is mango anthracnose, stemming from the pathogenic agent Colletotrichum gloeosporioides. Infected mango fruit typically exhibit dark, sunken lesions and black spots on their skin, which diminishes their quality and leads to considerable losses in the mango market. Therefore, this study aimed to characterise the physicochemical properties of Milk Gold mangoes infected with anthracnose disease. The samples were grouped into two: control samples and treated samples. The treated samples were inoculated with a spore solution of C. gloeosporioides (2.62 × 106 cell/ml) and incubated at room temperature (28ᵒC) for 7 days while control samples were injected with distilled, sterilised water. The progress of the anthracnose disease was evaluated at day 0 (after 1 hr of injection), 3, 5 and 7 of incubation period, and various physicochemical parameters, such as total soluble solids content (TSS), firmness, pH, colour, weight loss, and moisture content (MC) were measured. The results indicated that the anthracnose disease manifested as small black spots after 3 days of storage, and the flesh of the fruit began to rot severely by day 5 of storage. The increasing trends were observed in the TSS, pH, weight loss, and moisture content of the fruits, concomitant with a decrease in fruit firmness as ripening advanced. Notably, all colour parameter values (L*, a*, b*, c* and H*) indicated significant differences between the inoculated and control samples. With the rapid development of the symptoms, it is crucial to identify the disease at an early stage to apply the appropriate disease control measures during post-harvest handling.